(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In this article, it was presented how the media are present and related in the artistic process Geringonça, proposed by the Brazilian circus collective Instrumento de Ver from the identification and creation of categories that allowed to point out the proposed intermedialities. The concept of media was chosen as a mode of expression and objects that organize, transport, store or change our perception of the world and act as means for the production of meaning, treated within the perspective of intermediality. It was also considered the importance of studying different circus creative procedures to propose clues aimed at understanding circus writing and dramaturgy. From the research we could see that the writing of the circus show puts the intermedialities in evidence, emphasizing the contrast between different media, in an equivalence of importance.